Prolonged use of paracetamol and the prescribing patterns on rehabilitation facilities. Issue 23 (27th December 2021) - Jasat, Homairah; Thompson, John; Sonneborn, Olivia; Dayment, Jessica; Miller, Charne
Abstract: Aims and Objectives: The study investigated: (a) the usage patterns of paracetamol, and (b) the association between paracetamol use and patient outcomes such as liver and kidney functions among older people. Background: Paracetamol is a well‐known analgesic and antipyretic drug, with an excellent safety profile when used within its recommended dose. It is a commonly used drug by people aged over 65 years to treat chronic pain. Prolonged use of paracetamol in the elderly is poorly understood. As such, there is a genuine risk among older people of unintentional overdose. Methods: A retrospective analysis of medical records in rehabilitation wards was undertaken from 1 July 2016 to 30 June 2017. Patients' paracetamol use, prescribing patterns and biochemical results were analysed to assess for differences in admission and discharge biochemistry results. The TREND Statement was utilised to guide study reporting (Enhancing the QUAlity and Transparency Of health Research, 2021). Results: A total of 1119 patients were admitted for seven or more days in a metropolitan tertiary hospital in Melbourne. Almost three‐quarters (74%) of patients were administered paracetamol; 76.1% received 'Immediate‐Release Paracetamol' (IRP), and 23.9% were given 'Sustained‐Release Paracetamol' (SRP). A proportion (4.5%) of patients in both the IRP and SRP groups received more than the daily recommended dose. There were limited statistically significant differences between patients' admission and discharge biochemistry results; group or time differences were observed, which were indicative of improvements within the paracetamol group. Conclusion: Paracetamol was a commonly used medication among long‐stay elderly patients. Precaution to ensure paracetamol use does not exceed recommended daily doses is required. This study suggests that paracetamol used at a therapeutic level in older patients had limited, negative associations with liver and kidney function. Relevance to clinical practice: The clinical practice regarding prolonged use of paracetamol is ambitious. The increased risk of paracetamol toxicity among the frail elderly is a concern. Optimising the dose adjustment in the elderly is important to avoid adverse outcomes.